The Effects of a Self-Regulated Learning Teaching Unit on Students' Performance Calibration, Goal Attainment, and Attributions in Physical Education. Issue 1 (11th January 2022) - Kolovelonis, Athanasios; Goudas, Marios; Samara, Evdoxia
Abstract: This study examined the effects of a self-regulated learning teaching unit on students' performance calibration, goal attainment, and attributions in physical education. Participants were 101 fifth- and sixth-grade students who were randomly assigned to an experimental (57 students) and a control group (44 students). Calibration indexes were calculated based on students' estimated and actual performance in a basketball shooting test. The intervention included four sessions based on Zimmerman's four-level model of self-regulated learning. Experimental group students estimated more accurately their performance after the intervention compared to control group students while associations between calibration, goal attainment, and attributions were found. Results are discussed with reference to calibration and self-regulated learning in physical education. Practical implications and directions for future research are also provided.